2019
DOI: 10.3389/fmicb.2019.01875
|View full text |Cite
|
Sign up to set email alerts
|

Immunization With a Live-Attenuated RH:ΔNPT1 Strain of Toxoplasma gondii Induces Strong Protective Immunity Against Toxoplasmosis in Mice

Abstract: Toxoplasmosis, one of the most important health-threatening diseases worldwide, is caused by Toxoplasma gondii , which infects a wide range of warm-blooded animals and humans, leading to enormous health and socioeconomic concerns. T. gondii can establish chronic infection to evade the immune response in hosts. Once a chronic infection has been established, the available treatments cannot efficiently control this stage of T. gondii efficiently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Consistent with other live-attenuated T. gondii vaccines, mice vaccinated with RH∆gra17∆npt1 exhibited a high level of anti-T. gondii IgG antibodies [13,14,24,25]. These specific IgG antibodies play an important role in protection against T. gondii infection via hindering the attachment of the parasite to the host cells, limiting its ability to establish infection, and activation of the classical complement pathway [26].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Consistent with other live-attenuated T. gondii vaccines, mice vaccinated with RH∆gra17∆npt1 exhibited a high level of anti-T. gondii IgG antibodies [13,14,24,25]. These specific IgG antibodies play an important role in protection against T. gondii infection via hindering the attachment of the parasite to the host cells, limiting its ability to establish infection, and activation of the classical complement pathway [26].…”
Section: Discussionsupporting
confidence: 72%
“…Our data clearly demonstrate the ability of RH∆gra17∆npt1 to significantly reduce 91.4% of the parasite cyst burden compared to unvaccinated mice. In previous studies, it was demonstrated that vaccination using single-gene mutants, RH∆gra17 [13] and RH∆npt1 [24] resulted in 98.8% and 98.6% reduction in the parasite cyst burden, respectively. This finding suggests that although deletion of both gra17 and npt1 genes has considerably attenuated the virulence of the parasite, this was not paralleled by improvement in the double mutant's ability to limit the parasite cyst burden during latent infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and multiple stages of parasite infections (Wang et al, 2017(Wang et al, , 2018Xia et al, 2018b;Yang et al, 2019;Liang et al, 2020). In this study, PLK: gra9 vaccination induced a high level of immune response and resisted the infections of tachyzoites from type I or type II strains and cysts from type II strain.…”
Section: Discussionmentioning
confidence: 57%
“…Several studies on T. gondii vaccines have been done and reported in animal models. Although compared with nucleic acid vaccines ( Li et al, 2015 ; Zhang et al, 2015 ; Lu et al, 2017 ) and recombinant protein vaccines ( El Bissati et al, 2014 ; Tanaka et al, 2014 ; Wang et al, 2014a , b ), the higher protection against acute or chronic T. gondii infection provided by live attenuated vaccines ( Fox and Bzik, 2015 ; Lagal et al, 2015 ; Abdelbaset et al, 2017 ; Wang et al, 2017 , 2018 ; Xia et al, 2018b ; Yang et al, 2019 ; Liang et al, 2020 ) was highlighted both in short- and long-term vaccination using different strains in the mouse model. However, the safeness of these mutants still needs to be tested in animal models.…”
Section: Introductionmentioning
confidence: 99%